Negotiating Eschatology Online: Netizens' Reception of Ustadz Zulkifli Muhammad Ali's Youtube Da'wah - Ivan Sunata; Irta Sulastri; Bukhari; Nurus Shalihin; Wakidul Kohar (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study examines how YouTube audiences interpret eschatological Islamic da‘wah messages delivered by Ustadz Zulkifli Muhammad Ali within the digital public sphere. Employing a qualitative reception analysis, the research draws on Stuart Hall’s encoding/decoding framework to categorize audience interpretations into preferred, negotiated, and oppositional readings. The data were collected from user comments posted on the YouTube video “The End of the Age is Very Near” and systematically analyzed using NVivo 12 Plus. The findings reveal that negotiated and oppositional readings are more prominent than preferred readings, indicating a critical and reflexive mode of audience engagement. Many responses articulate skepticism, satire, and selective acceptance of the eschatological message, as viewers attempt to contextualize the da‘wah within broader social realities, religious knowledge, and contemporary concerns. These patterns suggest that digital da‘wah audiences do not merely consume religious messages but actively interpret, contest, and reframe them. This study contributes to the growing scholarship on digital da‘wah and religion online by demonstrating that religious meaning on social media is produced through dialogic and contested processes, where religious authority and interpretation are continuously negotiated in platform-mediated environments.